CHOICE OF LOCOMOTIVE PARK MAINTENANCE STRATEGY WHEN INTRODUCING THE SERVICE (Transport systems and technologies, 2021)
In operation, sometimes there are situations of uncertainty in assessing the technical condition of locomotive equipment and at the same time choosing the optimal strategy for its maintenance, including the possibility of using the service. Application of the concept of service gives the chance to stimulate work of all divisions of locomotive economy, to save all kinds of resources for operation of locomotives.According to this, the article substantiates the choice of strategy for maintaining the locomotive fleet using the provisions of the theory of statistical solutions. Game theory approaches were used to theoretically substantiate the transition to a service for decision-making in conflict situations and to determine the optimal strategy of behavior of each of the participants in this situation. Approaches to the choice of strategy for the maintenance of the locomotive fleet during the introduction of the service on the basis of the provisions of the theory of strategic games on the criterion of maximum efficiency were considered.It is shown on examples of the decision of some problems of a choice of maintenance strategy of locomotives for various industrial situations. It is concluded that a mixed strategy describes different situations best and allows to made rational decisions. It is also noted that the most effective approach to concretize the algorithm of actions is the complex application of the theory of strategic decisions, the theory of fuzzy sets, the theory of pattern recognition.
Keywords: locomotives, players, strategy games theory, strategy, service.